2018
DOI: 10.2147/cmar.s177320
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of combined preoperative platelet-to-lymphocyte ratio and lymphocyte-to-monocyte ratio in patients undergoing surgery with stage IB non-small-cell lung cancer

Abstract: BackgroundResearch indicates that the presence of a systemic inflammatory response plays an important role in predicting survival in patients with cancer. The aim of this study was to investigate the prognostic value of preoperative neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), prognostic nutritional index, and the combination of preoperative LMR and PLR (LMR-PLR) in predicting the survival of patients with stage IB non-small-cell lung cancer (NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…The present study has the limitations of being a single-centre retrospective study; also, although the preoperative testing that was used to obtain the ratios was the same for all patients, the ndings have not been validated in an independent cohort. The appropriate cut-off point for the ratio is di cult to establish, but according to our results, the value with the greatest sensitivity and speci city was 2.5; values above or below this showed signi cant differences in overall survival and disease-free survival, in line with other published studies [15][16][17]24,25].…”
Section: Discussionsupporting
confidence: 88%
“…The present study has the limitations of being a single-centre retrospective study; also, although the preoperative testing that was used to obtain the ratios was the same for all patients, the ndings have not been validated in an independent cohort. The appropriate cut-off point for the ratio is di cult to establish, but according to our results, the value with the greatest sensitivity and speci city was 2.5; values above or below this showed signi cant differences in overall survival and disease-free survival, in line with other published studies [15][16][17]24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Chen et al confirmed preoperative values of the above ratios in patients with IB stage, operated on due to NSCLC. The multi-factor analysis revealed prognostic values of LMR and PLR ratios in patients with this disease stage (11). Results of our study indicate that the PLR ratio is characterised with the highest preoperative prognostic value.…”
Section: Discussionmentioning
confidence: 51%
“…Pretreatment NLR is associated with the clinical outcomes of several therapeutic interventions in NSCLC patients, such as the response to platinum-based first-line chemotherapy in metastatic NSCLC patients, and the prognosis in operable NSCLC patients 27 , 28 . Moreover, inflammatory indices, including NLR, PLR, and LMR, are potential prognostic markers for lung cancer patients 29 32 . Our multivariate analysis demonstrated that high baseline NLR is an independent factor associated with poor PFS and OS.…”
Section: Discussionmentioning
confidence: 99%